(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Congenital rubella syndrome (CRS) is one of the most devastating congenital infections and yet the only one which is vaccine preventable. Rubella remains an important pathogen globally with approximately 100,000 cases of congenital rubella syndrome estimated by World Health Organization (WHO) to occur each year. It is a public health challenge for clinicians and policymakers across the developing world including Bangladesh. The clinical manifestations of CRS in newborn are a spectrum of congenital defects such as growth retardation, cardiac defects, cataracts, and hearing impairment. The development of vaccines and implementation of vaccination strategies have substantially reduced the incidence of the disease and in turn of CRS in developed countries. In Bangladesh CRS is still an under-recognized public health problem. Therefore, routine vaccination and other preventive strategies should be taken maintained and surveillance studies should be conducted to eliminate CRS from our country. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 41-45